The Morphological Development of the Uterus and Vagina in the Dogs - Dinç, Gürsel (Van Yüzüncü Yıl Üniversitesi, 1991)
In this study, anatomical and histological changes of uterus andvagina in female dogs, which occur during growth period were investigated. Thesedogs were divided into four groups in terms of their ages. These groups were asfollows: The ftrst 0-4 months, the second 4-8 months, the third 8-12 months and thelast group more than 12 months of age There were 5 dogs in each group.Right comu uteri was observed to be longer than left comu uteri. In laminapropria of vagina in only 0-4 and 4-8 months of ages groups irregular ducts wereobserved. Hymen was no observed between vagina and vestibulum vaginae. Cervixuteri of dog had simple tubular glands in lamina propria. Basal membrane wasfound to be always PAS positive all in parts of uterus.

Bu araştırmada, dişi kopeklerin uterus ve vagina 'larinda belirli gelişmedonemlerinde meydana gelen, anatomik ve histolojik değişimler incelendi. Kopekleryaşlarına gore 4 gruba bolündü. Birinci grup 0-4 aylık, ikinci grup 4-8 aylık, üçüncügrup 8-12 aylık ve son grup 12 aylık 'dan büyük kopeklerden oluştu. Her grup için 5kopek kullanıldi.Sağ cornu uteri, soldakinden daha uzun bulundu. Vagina ile vestibulumvaginae arasinda hymen gorülmedi. Vagina'nın lamina propria'sinda yalnız 0-4 ve4-8 aylık gruplarda geniş düzensiz boşluklar bulundu. Cervix uteri 'nin laminapropria'sında basit tubuler bezler mevcuttu. Bazal membran uterus'un tümbölümlerinde PAS pozitifdi.
KÖPEKLERDE UTERUS VE VAGİNA'NIN MORFOLOJİK GELİŞİMİ